Does Gender Matter: A Multi-Institutional Analysis of Viscoelastic Profiles for 1565 Trauma Patients With Severe Hemorrhage. Issue 3 (March 2022) - Smith, Alison; Duchesne, Juan; Marturano, Matthew; Lawicki, Shaun; Sexton, Kevin; Taylor, John R.; Richards, Justin; Harris, Charles; Moreno-Ponte, Oscar; Cannon, Jeremy W.; Guzman, Jessica F.; Pickett, Maryanne L.; et al.
Background: Viscoelastic tests including thromboelastography (TEG) and rotational thromboelastometry (ROTEM) are being used in patients with severe hemorrhage at trauma centers to guide resuscitation. Several recent studies demonstrated hypercoagulability in female trauma patients that was associated with a survival advantage. The objective of our study was to elucidate the effects of gender differences in TEG/ROTEM values on survival in trauma patients with severe hemorrhage. Methods: A retrospective review of consecutive adult patients receiving massive transfusion protocol (MTP) at 7 Level I trauma centers was performed from 2013 to 2018. Data were stratified by gender and then further examined by TEG or ROTEM parameters. Results were analyzed using univariate and multi-variate analyses. Results: A total of 1565 patients were included with 70.9% male gender (n = 1110/1565). Female trauma patients were older than male patients (43.5 ± .9 vs 41.1 ± .6 years, P = .01). On TEG, females had longer reaction times (6.1 ± .9 min vs 4.8 ± .2 min, P = .03), increased alpha angle (68.6 ± .8 vs 65.7 ± .4, P < .001), and higher maximum amplitude (59.8 ± .8 vs 56.3 ± .4, P < .001). On ROTEM, females had significantly longer clot time (99.2 ± 13.7 vs 75.1 ± 2.6 sec, P = .09) and clot formation time (153.6 ± 10.6 sec vs 106.9 ± 3.8 sec, P < .001). When comparing by gender, no difference for in-hospital mortality was found for patients in the TEG or ROTEM group ( P > .05). Multivariate analysis showed no survival difference for female patients (OR 1.11, 95% CI .83-1.50, P = .48). Conclusions: Although a difference between male and females was found on TEG/ROTEM for certain clotting parameters, no difference in mortality was observed. Prospective multi-institutional studies are needed.